1996
DOI: 10.1111/j.2044-8295.1996.tb02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Kirton's A–I theory: Evidence bearing on the style/level and factor composition issues

Abstract: ATwo central issues concerning M. J. Kirton's adaption-innovation (A-I) theory, the style vs. level issue and the issue of factor number, are reviewed in terms of existing empirical research. Direct tests of those two issues as they apply to A-I theory indicate that Kirton's position holds. Although the directly applicable evidence is not extensive, that which is available supports Kirton's distinction between style and level of creativity and a simple three-factor structure underlying the hypothesized A1 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 4 publications
0
16
0
3
Order By: Relevance
“…High conformity to rules will likely produce adaptive or incremental innovations and solutions. Low conformity to rules, on the contrary, enhances originality, resulting in original innovations (Mudd, 1996;Rosenfeld, Winger-Bearskin, Marcic, & Braun, 1993). Entrepreneurs display a high degree of nonconformity as compared to nonentrepreneurs.…”
Section: Nonconformitymentioning
confidence: 99%
“…High conformity to rules will likely produce adaptive or incremental innovations and solutions. Low conformity to rules, on the contrary, enhances originality, resulting in original innovations (Mudd, 1996;Rosenfeld, Winger-Bearskin, Marcic, & Braun, 1993). Entrepreneurs display a high degree of nonconformity as compared to nonentrepreneurs.…”
Section: Nonconformitymentioning
confidence: 99%
“…Sehingga peluang dianggap sebagai cara untuk menjawab ketidak sempurnaan pasar, teori ini menggangap bahwa setiap orang dapat mengambil peluang. Pendapat ini dikritik oleh beberapa peneliti, karena tidak semua orang mampu mengakses informasi dalam kondisi asymmetric information,dan terjadi information gap, sehingga hanya sebahagian orang yang mampu mengidentifikasikan peluang dan sebagian menemukan kegagalan (Neergaard, Helle and Ulhøi, 2007). Hal ini sejalan dengan (Barney, Jay, B, et all,2011) dengan pendekatan Resurces Based Viewmasalah dalam OR adalah adalah kewaspadaan entrepreneurial bagaimana membawa dari philosofi ide-ide ke bisnis riil, yang mengalami perubahan.…”
Section: Konstruksi Kognitif Opportunity Recognition(or)unclassified
“…KAI adalah teori yang membantu untuk menjelaskan adanya perbedaan kreativitas diantara anggota tim dan menyatukannya melalui kolaborasi untuk menciptakan inovasi (Stum,K., 2009). Kirton-adaption-innovation theory, pada awalnya teori yang dikembangkan untuk menentukan gaya kognitif dan selanjutnya digunakan dalam berbagai penelitian empirik yang menjelaskan hubungan cognitive style dengan kreativitas dan inovasi serta kolaborasi jejaring terhadap kecenderungan pemecahan masalah (Pettigrew, 1988;Odenwald, 2010;Mudd, 1996).Sebagaimana juga dinyatakan oleh Jablokow and Booth mendefinisikan kesenjangan kognitif (a) perbedaan antara kesulitan terhadap pemecahaan masalah yang spesifik dan kemampuan kognitif pemecahan masalah untuk mencari solusi. (b) perbedaan antara gaya kognitif terhadap pemecah masalah masing-masing (Jablokow dan Booth, 2006).…”
Section: Konstruksiunclassified
“…He treats these two dimensions orthogonally and a significant body of research, conducted both by Kirton and other researchers (e.g., Torrance, 1982;Torrance & Horng, 1980), generally confirms this ascertainment. Exhaustive discussion in research with respect to the level-style problem can be found both in the works of Kirton himself (2003) and his acolytes (Isaksen & Dorval, 1993, Mudd, 1996. Mudd (1996) in his study of relationships between creativity level and style, relies on the research based on factor analyses which ordinarily indicate level (e.g., results in such creativity tests as TTCT) and style (KAI, or the MBTI creativity index) typically load on different factors.…”
mentioning
confidence: 99%
“…Exhaustive discussion in research with respect to the level-style problem can be found both in the works of Kirton himself (2003) and his acolytes (Isaksen & Dorval, 1993, Mudd, 1996. Mudd (1996) in his study of relationships between creativity level and style, relies on the research based on factor analyses which ordinarily indicate level (e.g., results in such creativity tests as TTCT) and style (KAI, or the MBTI creativity index) typically load on different factors. Results like this are provided by Kirton's (1987) re-analysis of data provided by Torrance and Horng (1980), where independence of level and style was confirmed -despite a rather small sample (N = 33).…”
mentioning
confidence: 99%